A combination of initial and follow-up physiotherapist examination predicts physician-determined time to return to play after hamstring injury, with no added value of MRI. Issue 7 (3rd February 2016) - Jacobsen, Phil; Witvrouw, Erik; Muxart, Patrice; Tol, Johannes L; Whiteley, Rod
Abstract : Background: Previous studies investigating prediction of return to play after acute hamstring injury were limited by examining a single postinjury clinical and MRI evaluation. We evaluated the added value of including follow-up clinical evaluation when predicting return to play. Methods: A range of clinical and MRI parameters were prospectively investigated for an association with the time to return to play in 90 athletes with MRI positive hamstring injuries undergoing a criteria-based rehabilitation programme. Clinical evaluation was performed within 5 days of injury and 7 days after this initial assessment (follow-up clinical evaluation). The association between possible prognostic parameters and the time to return to play was assessed with a multiple linear regression model. Results: Data of 90 athletes were available for analysis. At the first physiotherapy appointment, a combination of three demographic and six clinical variables explained 50% of the variance (±19 days) in the time to return to play. At follow-up assessment (7 days), a combination of 10 clinical and demographic variables explained 97.0% of the variance (±5 days) in time to return to play. In order of importance, the variables were: change in strength during the first week for the 'mid-range' test, peak isokinetic knee flexion torque of the uninjured leg, maximum pain at the time of injury, number of days to walk pain free, playing the sport of football, strength performing the 'inner range' hamstring test at day 1, presence of pain on a single leg bridge at day 7 or its absence during a single leg bridge, delay in starting treatment and percentage of strength in the 'outer range' test compared to the healthy leg. No MRI variables were retained in any of these analyses. MRI variables alone explained 8.6% of the variance—which is unhelpful to players and coaches. Summary: The combination of initial and 7-day follow-up clinical evaluation is clinically helpful in predicting time to return to play (±5 days) following acute hamstring injury. MRI offered no useful clinical information regarding return to play duration in this cohort. Trial registration number: NCT01812564.